1995
DOI: 10.1557/proc-412-281
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Separated Tc and Cs/Sr in Synroc

Abstract: In some radwaste applications, such as immobilization of U.S. Tank wastes using vitrification, Tc and Cs/Sr are likely to be separated out from HLW supernates. Simplified Synroc preparations can be devised for the immobilization of separated Tc and Cs/Sr, either together or individually. Under suitably reducing processing conditions, Tc can be immobilized, as metal or Tc4+. The volatility of Tc and Cs/Sr in Synroc processing is very restricted.In Synroc-C, designed for Purex high-level reprocessing wastes, Tc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Australia, 1996 [12] In 1996, ANSTO reported on immobilization of Tc, Cs and Sr in Synroc. Cs-doped samples were made by the sol-gel route in which an alkoxide based liquid precursor plus nitrates and TcO 4 -2 is hydrolyzed, dried, calcined under reducing conditions at 600-750 o C and hot pressed at 1200 o C/20 MPa in stainless steel.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Australia, 1996 [12] In 1996, ANSTO reported on immobilization of Tc, Cs and Sr in Synroc. Cs-doped samples were made by the sol-gel route in which an alkoxide based liquid precursor plus nitrates and TcO 4 -2 is hydrolyzed, dried, calcined under reducing conditions at 600-750 o C and hot pressed at 1200 o C/20 MPa in stainless steel.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…[11] A variation on this is known as the standard sol-gel route in which an alkoxide based liquid precursor is hydrolyzed by mixing with an aqueous waste stream, dried, calcined under reducing conditions and hot-pressed in metal bellows at 1200 o C / 14-20 MPa after adding 2 wt% Ti metal as an oxygen getter. [12] The Synroc precursor can also be made via a chemical processing route involving Ti and Zr alkoxide hydrolysis in the presence of NaOH to form a sodium titanate/zirconate powder which acts as a cation exchanger for Al, Ba, and Ca waste nitrate solutions. This form is dried and then calcined under reducing conditions and hot pressed and sintered at 1100-1170°C, with the addition of 2 wt% Ti to lower the mobility of the volatiles and keep Mo metallic to avoid the formation of water soluble molybdates.…”
Section: Sinteringmentioning
confidence: 99%
“…The fractional release of technetium from the spent fuel pin is lower than for the titanate pellets. Tc-leachrates in Synroc-C [8], doped with 2 wt% Tc, have been measured in the order of 6E-4 g/m 2 .d and 2E-4 g/m 2 .d for oxidising and anoxic conditions respectively for a contact period of about 40 days. Due to the differing test UO2 spent fuel (Cui et al) circumstances, also with respect to the oxygen-deficient atmosphere applied for leaching of the spent fuel pin, the lower leach rate does not necessarily justify the conclusion that UO 2 is a better host phase for technetium.…”
Section: Comparisonmentioning
confidence: 99%
“…Recently, Hart et al [9] reported that in the SYNROC process, 99 Tc with a loading of 20 000 ppm can be stabilized so that leach rates, from PCT tests, can reach as low as 10 À4 g/m 2 d. It is believed that, in SYNROC, 99 Tc goes into the solid solution with rutile phase and is then chemically fixed, leading to its lower leachability. Uncertainties remain about the volatility of 99 Tc in the high-temperature borosilicate glasses and SYNROC processes.…”
Section: Introductionmentioning
confidence: 99%